Detection of very high energy gamma-ray emission from the gravitationally lensed blazar QSO B0218+357 with the MAGIC telescopes - Ahnen, M. L.; Ansoldi, S.; Antonelli, L. A.; Antoranz, P.; Arcaro, C.; Babic, A.; Banerjee, B.; Bangale, P.; Barres de Almeida, U.; Barrio, J. A.; Becerra González, J.; Bednarek, W.; et al. (EDP Science, 2022)
Context. QSO B0218+357 is a gravitationally lensed blazar located at a redshift of 0.944. The gravitational lensing splits the emitted radiation into two components that are spatially indistinguishable by gamma-ray instruments, but separated by a 10-12 day delay. In July 2014, QSO B0218+357 experienced a violent flare observed by the Fermi-LAT and followed by the MAGIC telescopes.
Aims: The spectral energy distribution of QSO B0218+357 can give information on the energetics of z 1 very high energy gamma-ray sources. Moreover the gamma-ray emission can also be used as a probe of the extragalactic background light at z 1.
Methods: MAGIC performed observations of QSO B0218+357 during the expected arrival time of the delayed component of the emission. The MAGIC and Fermi-LAT observations were accompanied by quasi-simultaneous optical data from the KVA telescope and X-ray observations by Swift-XRT. We construct a multiwavelength spectral energy distribution of QSO B0218+357 and use it to model the source. The GeV and sub-TeV data obtained by Fermi-LAT and MAGIC are used to set constraints on the extragalactic background light.
Results: Very high energy gamma-ray emission was detected from the direction of QSO B0218+357 by the MAGIC telescopes during the expected time of arrival of the trailing component of the flare, making it the farthest very high energy gamma-ray source detected to date. The observed emission spans the energy range from 65 to 175 GeV. The combined MAGIC and Fermi-LAT spectral energy distribution of QSO B0218+357 is consistent with current extragalactic background light models. The broadband emission can be modeled in the framework of a two-zone external Compton scenario, where the GeV emission comes from an emission region in the jet, located outside the broad line region.